2016
DOI: 10.1155/2016/6762731
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Reveals Effects of Exogenous Hematin on Anthocyanin Biosynthesis during Strawberry Fruit Ripening

Abstract: Anthocyanin in strawberries has a positive effect on fruit coloration. In this study, the role of exogenous hematin on anthocyanin biosynthesis was investigated. Our result showed that the white stage of strawberries treated with exogenous hematin had higher anthocyanin content, compared to the control group. Among all treatments, 5 μM of hematin was the optimal condition to promote color development. In order to explore the molecular mechanism of fruit coloring regulated by hematin, transcriptomes in the hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…For example, the fresh weight, fruit color and °Brix value of berries were enhanced by foliage application of 100 mg/L ALA, at flowering period in a 2-year-old grapevines plants (Vitis vinifera L.) (Watanabe et al 2006). During fruit growth and maturation, the coloring of pannexterna is due to anthocyanin biosynthesis and accumulation, which can be affected by light and plant hormone (including abscisic acid and naphthaleneacetic acid) (Jeong et al 2004;Vimolmangkang et al 2014;Li et al 2016). Genes in 'Fuji' apple skin, including enzyme genes (Pal, Chs and Ufgt) and transcription factors (Myb, bHLH and Wd40) related to anthocyanin biosynthesis, were all upregulated by ALA solution sprayed on the surface of fruits (Xie et al 2013;Chagné et al 2016).…”
Section: Fruit Coloringmentioning
confidence: 99%
“…For example, the fresh weight, fruit color and °Brix value of berries were enhanced by foliage application of 100 mg/L ALA, at flowering period in a 2-year-old grapevines plants (Vitis vinifera L.) (Watanabe et al 2006). During fruit growth and maturation, the coloring of pannexterna is due to anthocyanin biosynthesis and accumulation, which can be affected by light and plant hormone (including abscisic acid and naphthaleneacetic acid) (Jeong et al 2004;Vimolmangkang et al 2014;Li et al 2016). Genes in 'Fuji' apple skin, including enzyme genes (Pal, Chs and Ufgt) and transcription factors (Myb, bHLH and Wd40) related to anthocyanin biosynthesis, were all upregulated by ALA solution sprayed on the surface of fruits (Xie et al 2013;Chagné et al 2016).…”
Section: Fruit Coloringmentioning
confidence: 99%
“…Therefore, one or more components in ALA metabolic pathways may be involved in the regulation of plant tolerance against salt stress. During fruit coloring, hematin (an exogenous heme) may improve anthocyanin accumulation in strawberries (Li et al ). Heme oxygenase‐1 (HO‐1) promotes anthocyanin accumulation in radish hypocotyls (Liu et al ).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, RNA-Seq technology has been used to study fruit development and ripening ( Kang et al, 2013 ; Pillet et al, 2015 ; Li et al, 2016 ; Estrada-Johnson et al, 2017 ; Hartl et al, 2017 ). In this study, 91,790 unigenes were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…FaTCP11 , FaPCL1-like , and FaSCL8 modulate the metabolism of strawberry flavonoids by regulating the expression of flavonoid pathway genes based on a transcriptome correlation network analysis of ripe strawberry fruits ( Pillet et al, 2015 ). Another application of transcriptome analysis in the strawberry anthocyanin biosynthesis pathway reveals that exogenous hematin promotes fruit coloring through multiple related metabolic pathways including anthocyanin biosynthesis and hormone signaling transduction, among others ( Li et al, 2016 ). In red-fruited and natural white-fruited strawberry varieties, transcriptome analysis showed that the genes related to the polyphenol biosynthesis pathway may interact with anthocyanin biosynthesis, flavor formation and fruit softening to regulate the fruit ripening process ( Hartl et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%